Structural studies of Helicase NS3 variants from Hepatitis C virus genotype 3 in virological sustained responder and non-responder patients - Provazzi, Paola J.S. [UNESP]; Arcuri, Helen A.; De Carvalho-Mello, Isabel Maria V.G.; Pinho, Joo Renato R.; Nogueira, Maurício L.; Palma, Mario Sergio [UNESP]; Rahal, Paula [UNESP] (Springer Nature, 2010)
Background. About 130 million people are infected with the hepatitis C virus (HCV) worldwide, but effective treatment options are not yet available. One of the most promising targets for antiviral therapy is nonstructural protein 3 (NS3). To identify possible changes in the structure of NS3 associated with virological sustained response or non-response of patients, a model was constructed for each helicase NS3 protein coding sequence. From this, the goal was to verify the interaction between helicases variants and their ligands. Findings. Evidence was found that the NS3 helicase portion of non-responder patients contained substitutions in its ATP and RNA binding sites. K210E substitution can cause an imbalance in the distribution of loads, leading to a decrease in the number of ligations between the essential amino acids required for the hydrolysis of ATP. W501R substitution causes an imbalance in the distribution of loads, leading and forcing the RNA to interact with the amino acid Thr269, but not preventing binding of ribavirin inhibitor. Conclusions. Useful information is provided on the genetic profiling of the HCV genotype 3, specifically the coding region of the NS3 protein, improving our understanding of the viral genome and the regions of its protein catalytic site. © 2010 Rahal et al; licensee BioMed Central Ltd.
Keywords: Hepatitis C virus; Hepatitis C virus genotype 3